2006
DOI: 10.1016/j.transproceed.2006.10.147
|View full text |Cite
|
Sign up to set email alerts
|

T-Cell Depletion Eliminates the Development of Cardiac Allograft Vasculopathy in Mice Rendered Tolerant by the Induction of Mixed Chimerism

Abstract: We previously demonstrated that cardiac allografts to fully tolerant chimeric mice developed cardiac allograft vasculopathy (CAV). Here we begin to examine which components of the immune system are responsible for the pathogenesis of CAV in such tolerant recipients. B10.A/B6 mixed chimeric mice were created by receiving injections of bone marrow cells from B10.A (H-2 k ) mice given to C57BL/6 (B6; H-2 b ) mice with some preparations. B10.A skin grafts were first placed onto B10.A/ B6 mixed chimeric recipients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Chronic allograft vasculopathy (CAV) remains the major factor limiting long-term survival of heart allografts in humans (1,2) despite advances therapy. Mechanistic studies in mouse heart allografts have demonstrated three distinct pathways to CAV: T cells with minor antigen mismatch (3,4), natural killer (NK) cells with parent to F1 grafts (5,6) and MHC antibody with adoptive transfer of donor specific antibody (DSA) (4,7,8). Antibody-mediated CAV was demonstrated initially by adoptive transfer of polyclonal or monoclonal DSA in normal and immunodeficient recipients of heart allografts (8) and in human vascular allografts in mice (9).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic allograft vasculopathy (CAV) remains the major factor limiting long-term survival of heart allografts in humans (1,2) despite advances therapy. Mechanistic studies in mouse heart allografts have demonstrated three distinct pathways to CAV: T cells with minor antigen mismatch (3,4), natural killer (NK) cells with parent to F1 grafts (5,6) and MHC antibody with adoptive transfer of donor specific antibody (DSA) (4,7,8). Antibody-mediated CAV was demonstrated initially by adoptive transfer of polyclonal or monoclonal DSA in normal and immunodeficient recipients of heart allografts (8) and in human vascular allografts in mice (9).…”
Section: Introductionmentioning
confidence: 99%
“…However, conflicting findings have been obtained in two studies, implying that deletion of recipient T cells specific for allogeneic MHC molecules on donor APCs (i.e., direct allorecognition) may not be sufficient to maintain allograft tolerance in macrochimeric mice. Uehara et al reported that skin and heart allografts accepted by mice displaying stable mixed chimerism later developed cardiac allograft vasculopathy (chronic rejection) dependent on the presence of host CD4 + T cells [24]. More recently, Shinoda et al found that depleting Foxp3 + T cells abrogated tolerance of skin and heart allografts in stable mixed chimeras without an associated loss of mixed chimerism [25].…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, chronic cardiac allograft rejection involves predominantly vascular damage with or without parenchymal fibrosis (51,52). CAV appears to have components of humoral, cellular, and NK cell-mediated mechanisms (1,53). After pruning of alloreactive CD4 ϩ T cells while there was chronic fibrosis with some cellular infiltration, there was minimal CAV.…”
Section: Discussionmentioning
confidence: 99%